Towards a Theory of Value as a Commons. Issue 1 (7th September 2022) - Pazaitis, Alex; Kostakis, Vasilis; Drechsler, Wolfgang
This essay aspires to explore the contours of a theory of value based on the commons. Its starting point is an understanding of value as a means through which empirical economic phenomena are guided by an underlying structure. Value is understood as the way people's actions become meaningful to them within a broader social whole defined by the said structure. We approach the digital commons as such a social whole, articulated by distinct value practices, emerging within, yet at odds with, capitalism. We employ interpretivist analysis to identify elements of a theory of value in the digital commons, borrowing from diverse theoretical perspectives, and utilizing the results of original research conducted elsewhere. The conceptualization of value as a commons places value itself in the commons, as a collective agreement, being part of the shared rules and norms guiding collective action. Our aim is twofold. First, to reinvigorate discussions on value in the study of social and economic affairs. Second, to formulate a perception of value that could guide meaningful and sustainable transformations of future social and economic arrangements based on the commons.